Paradoks HAM Dalam Hubungan Internasional: Humanitarian Intervention Di Suriah - Maulana, Faisal (Journal of Law, Administration, and Social Science, 2024)
Human rights have been approved as an achievement for every nation according to the 1945 UN Charter. So the UN formed the UN Security Council which has the responsibility to protect parties who are victims of human rights violations due to war crimes through humanitarian intervention and R2P. However, several things hinder the creation of a world without human rights violations, especially in the international system. In the end, this creates a new paradox in the goals of the UN formed based on the 1945 UN Charter. HAM telah disetujui sebagai pencapaian bagi setiap bangsa menurut Piagam PBB 1945. Sehingga PBB membentuk Dewan Keamanan PBB yang memiliki tanggung jawab untuk melindungi pihak-pihak yang menjadi korban pelanggaran HAM atas kejahatan perang melalui intervensi humanitarian dan R2P. Meskipun begitu, beberapa hal menjadi penghalang terciptanya dunia tanpa pelanggaran HAM, khususnya dalam sistem internasional. Pada akhirnya, hal ini menciptakan paradoks baru dalam tujuan PBB terbentuk berdasarkan Piagam PBB 1945.